Semiótica do discurso científico: Um estudo sobre novas perspectivas para a análise documental de conteúdo - Alves, Roberta Caroline Vesú [UNESP]; De Moraes, João Batista Ernesto [UNESP]; De Almeida, Carlos Cândido [UNESP] (My University, 2014)
Greimas Semiotic offers procedures for the analysis of different types of texts and discourses. For this reason, this study aimed to analyze the production of sense from scientific discourse, explained by Greimas Semiotics and Generative Sense Course, seeking to develop a new perspective on the identification of aboutness in Documentary Content Analysis and Information Science. The method used was exploratory and bibliographic review. Results show that the analysis of scientific discourse contributes to the identification of aboutness in Documentary Content Analysis, using Greimas Semiotics and Generative Sense Course.
Semiotic of scientific discourse: A study on new perspectives for documentary content analysis
Keywords: Aboutness; Documentary content analysis; Generative sense course; Greimas semiotics; Scientific discourse